Correlation of emotional quotient and personality profiles with medical students' future performance - Rahim, Ahmad Fuad Abdul; Esa, Ab Rahman; Mey, See Ching
Objective: To determine the internal consistency and construct validity of the USMEQ-i among medical program applicants. It is hoped that the inventory is a reliable and valid instrument that can be used to measure emotional quotient of the applicants to assist in the selection process of medical students. Methodology: Cross sectional study was done on 486 applicants to the medical course in Universiti Sains Malaysia (USM). The items of USMEQ-i were framed from literature review. The USMEQ-i was administered just after the interview session of the student selection process. The Cronbach's alpha reliability analysis and factor analysis were applied to measure internal consistency and construct validity respectively. The analysis was done using Statistical Package for Social Science (SPPS) version 12.0.1. Result: A total of 469 applicants participated in this study. Factor analysis showed that items were well loaded into eight constructs as their factor loadings more than 0.3. The Cronbach's alpha value of the USMEQ-i was 0.95. The Cronbach's alpha values of emotional control, emotional maturity, emotional conscientiousness, emotional awareness, emotional commitment, emotional fortitude, emotional expression and faking index domains were 0.90, 0.82, 0.83, 0.79, 0.77, 0.66, 0.60 and 0.83 respectively. These findings reinforced the validity and reliability evidence of USMEQ-i in measuring EQ. Conclusion: The USMEQ-i shows good psychometric values. It is a valid and reliable instrument to measure EQ of medical program applicants. It is a promising psychometric instrument that can be used as an instrument to assist in the student selection.